2021
DOI: 10.1016/j.jare.2021.01.003
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs secreted by human embryos could be potential biomarkers for clinical outcomes of assisted reproductive technology

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 62 publications
(71 reference statements)
0
18
0
Order By: Relevance
“…The model with the minimum AIC value was the preferred model, and genera in this model were viewed as the potential biomarkers. Receiver operating characteristic (ROC) curve analysis was conducted to evaluate the diagnostic performance of the identified potential biomarkers ( Kumstel et al., 2020 ; Wang et al., 2021 ; Fang et al., 2021 ). The area under the curve (AUC) was used to assess the diagnostic performance: 0.9–1, excellent; 0.8–0.9, good; 0.7–0.8, fair; 0.6–0.7, poor; and 0.5–0.6, failed.…”
Section: Methodsmentioning
confidence: 99%
“…The model with the minimum AIC value was the preferred model, and genera in this model were viewed as the potential biomarkers. Receiver operating characteristic (ROC) curve analysis was conducted to evaluate the diagnostic performance of the identified potential biomarkers ( Kumstel et al., 2020 ; Wang et al., 2021 ; Fang et al., 2021 ). The area under the curve (AUC) was used to assess the diagnostic performance: 0.9–1, excellent; 0.8–0.9, good; 0.7–0.8, fair; 0.6–0.7, poor; and 0.5–0.6, failed.…”
Section: Methodsmentioning
confidence: 99%
“…Then, in 2019, Abu-Halima and his colleagues reported that the abundance of miR-19b-3p was significantly lower in spent culture medium (SCM) samples associated with positive pregnancy (12). Fang et al indicated that hsa-miR-26b-5p and hsa-miR-21-5p could serve as potential biomarkers for reproductive outcomes by detecting the miRNA profiles in the human embryo culture media (13).…”
Section: Introductionmentioning
confidence: 99%
“…In their study, pregnancy outcomes and miRNA profiles were correlated only when intracytoplasmic sperm injection (ICSI) was used, which could limit the use of miRNA as a biological marker for pregnancy outcomes [ 22 ]. Fang et al also concluded that certain miRNA molecules (namely, has-miR-26b-5p and has-miR-21b-5p) could serve as potential biomarkers for reproductive outcomes [ 23 ].…”
Section: Emerging Biological Markers In Secmmentioning
confidence: 99%
“…These authors cumulatively agree that miRNA could serve as a good non-invasive marker of the quality of the preimplantation embryo, as it is stable, easily accessible, and easily detected. More research is needed to standardize the tests and to better understand the role of these molecules [ 22 , 23 , 24 ].…”
Section: Emerging Biological Markers In Secmmentioning
confidence: 99%